Fiona Barclay. Writing Postcolonial France. Haunting, Literature, and the Maghreb. Lanham, Md.: Lexington Books, 2011. xliv + 152 pp. - Anna Rocca (Studies in 20th & 21st Century Literature, 2014)
Review of Fiona Barclay. Writing Postcolonial France. Haunting, Literature, and the Maghreb. Lanham, Md.: Lexington Books, 2011. xliv + 152 pp.
Keywords: haunting; postcolonial; French literature